Kajian Eksperimen Pengaruh Variasi Diameter Stagger Silinder Di Depan Returning Blade Turbin Angin Savonius Overlap Tipe Myring N=1 - Nurman Dwi Harmaji; Priyo Agus S; Projek Priyonggo Sumangun (Proceedings Conference on Marine Engineering and its Application, 2023)
Based on previous research, the performance of Savonius Overlap wind turbine withadditional cylinders had increased but it could still be improved to reach the highest performance.Based on this condition, this experiment was carried out by using a Savonius wind turbine bychanging blade with Myring n = 1 and adding an Overlap Ratio of 0.3 to the turbine blade. Itsdiameter and height are 40 cm. The stagger cylinder is placed with a distance ratio of S/d 1.7 anduses various diameter ratio 0.4 0.5 0.6 and 0.7. The wind speed is arranged by varying the speedof 5 , 6 and 7 m/s. This experiment was conducted to determine effect of additional circularcylinder to Coefficient Power (Cp) and Coefficient Torque (Ct). The final result shows that thebest performance increase occurs in the variation of interfering cylinder diameter ratio ds/D = 0.4with a wind speed of 6 m/s. The increase in the Coefficient Torque (Ct) is 9.58% and theCoefficient Power (Cp) is 21.56% for the Savonius Myring wind turbine n = 1 Overlap withoutinterfering cylinders.